2010
DOI: 10.1073/pnas.1009490107
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylguanosine capping selectively promotes expression of Rev-dependent HIV-1 RNAs

Abstract: 5′-mRNA capping is an early modification that affects pre-mRNA synthesis/splicing, RNA cytoplasmic transport, and mRNA translation and turnover. In eukaryotes, a 7-methylguanosine (m7G) cap is added to newly transcribed RNA polymerase II (RNAP II) transcripts. A subset of RNAP II-transcribed cellular RNAs, including small nuclear RNA (snRNA), small nucleolar RNA (snoRNA), and telomerase RNA, is further hypermethylated at the exocyclic N2 of the guanosine to create a trimethylguanosine (TMG)-capped RNA. Some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 67 publications
2
97
0
1
Order By: Relevance
“…As a proof of concept, we tested three known methyltransferase inhibitors and found that only (-)-epigallocatechin gallate inhibited hTGS1. Since specific RNA methyltransferases inhibitors, e.g., for Dengue virus methyltransferase 29 or even for PIMT 30 could be of therapeutic interest, a high-throughput screen is desirable to test large compound libraries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof of concept, we tested three known methyltransferase inhibitors and found that only (-)-epigallocatechin gallate inhibited hTGS1. Since specific RNA methyltransferases inhibitors, e.g., for Dengue virus methyltransferase 29 or even for PIMT 30 could be of therapeutic interest, a high-throughput screen is desirable to test large compound libraries.…”
Section: Resultsmentioning
confidence: 99%
“…29 Even some HIV-1 RNAs have been found to be trimethylguanosine-capped and acquisition of this cap hypermethylations facilitates the optimal expression of these RNAs. 30 An assay to test potential small molecule inhibitors of RNA methyltransferases including trimethylguanosine synthases in high-throughput could thus speed up the discovery of novel inhibitors.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, Exportin-1 also has high affinity for the (TMG)-capped small nucleolar RNA (snoRNA) U3 in the nucleus and transports it from Cajal bodies to the nucleoli (32). Another study showed that TGS1 enhances Rev-dependent HIV-1 RNA expression by (TMG)-capping viral mRNAs in the nucleus, thereby increasing recognition by Exportin-1 for transport to the cytoplasm (33).…”
Section: Significancementioning
confidence: 99%
“…However, this is not the case and TMG-capping of viral mRNAs associates with an increased expression of HIV-1 structural proteins. 151 Although the mechanism by which these TMG-capped viral mRNAs recruit the translational machinery was not studied, it is tempting to speculate that translation initiation from the TMG-HIV-1 RNAs could take place by a cap-independent IRES-mediated mechanism.…”
mentioning
confidence: 99%
“…PIMT hypermethylates the m 7 G RNA-cap to generate a pool of trimethylguanosine (TMG; m 2, 2,7 guanosine)-cap containing viral mRNAs. [151][152][153] TMG-capped-RNAs are known to translate poorly, 154 due to the inefficient recognition of the trimethyl by the cap-binding protein eIF4E. [155][156][157][158] As a consequence, it would be predicted that TMG-HIV-1 RNAs would be inefficiently translated resulting in a decrease of viral expression.…”
mentioning
confidence: 99%